Case Report: Coil embolization of ascending aortic pseudoaneurysm in patient with Behcet's disease - Kang, Mengyang; Zhang, Bo; Pang, Honggang; Hu, Huishe; Zhang, Junbo (Frontiers in Cardiovascular Medicine, 2024)
Background: Behcet’s disease (BD) is a systematic vasculitis that affects vessels with various sizes, presenting as venous thrombosis and arterial pseudoaneurysms. The most severe manifestation in BD is ascending aortic pseudoaneurysm, which is associated with high risks of rupture and mortality. Case Presentation: We present a case of ascending aortic pseudoaneurysm in a 50-year-old patient with BD. After preoperative evaluation, coil embolization was successfully performed to treat the pseudoaneurysm, resulting in a satisfactory outcome at the 1-year follow-up. Conclusion: Coil embolization serves as an effective treatment option for ascending aortic pseudoaneurysm in BD when open surgical repair and stent graft placement are unsuitable.